2023
DOI: 10.1111/pce.14526
|View full text |Cite
|
Sign up to set email alerts
|

High ambient temperature impacts on flowering time in Brassica napus through both H2A.Z‐dependent and independent mechanisms

Abstract: Knowledge concerning the integration of genetic pathways mediating the responses to environmental cues controlling flowering initiation in crops is scarce. Here, we reveal the diversity in oilseed rape (OSR) flowering response to high ambient temperature. Using a set of different spring OSR varieties, we found a consistent flowering delay at elevated temperatures.Remarkably, one of the varieties assayed exhibited the opposite behaviour. Several FT-like paralogs are plausible candidates to be part of the florig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In this sense, it is not surprising that different plants may utilize distinct transcription factors employing unique sets of epigenetic modifications to achieve proper FT regulation at high temperatures. Indeed, in their study, Abelenda et al (2023) have found that the promoter of BnaFTA2 (where transcription factors normally bind) is responsible for its regulation by high temperatures, and the levels of chromatin accessibility and H3K4me3 at the BnaFTA2 locus positively correlate with its expression changes. Key basic knowledge breakthroughs in understanding thermal regulation of flowering will be made by identifying transcription factors that directly control thermal‐mediated FT transcription in different plant species, followed by characterizing their regulatory mechanisms.…”
Section: Organism Temperature Change Typical Accession Impact On Flow...mentioning
confidence: 99%
See 3 more Smart Citations
“…In this sense, it is not surprising that different plants may utilize distinct transcription factors employing unique sets of epigenetic modifications to achieve proper FT regulation at high temperatures. Indeed, in their study, Abelenda et al (2023) have found that the promoter of BnaFTA2 (where transcription factors normally bind) is responsible for its regulation by high temperatures, and the levels of chromatin accessibility and H3K4me3 at the BnaFTA2 locus positively correlate with its expression changes. Key basic knowledge breakthroughs in understanding thermal regulation of flowering will be made by identifying transcription factors that directly control thermal‐mediated FT transcription in different plant species, followed by characterizing their regulatory mechanisms.…”
Section: Organism Temperature Change Typical Accession Impact On Flow...mentioning
confidence: 99%
“…The reason for diversification in flowering responses to high temperatures is not clear, and it may be attributed to plant‐specific growth habits, life cycles, and breeding backgrounds that eventually differentiate the regulatory mechanisms of flowering by high temperatures. Nevertheless, studies so far all suggest a central role of FT ‐like genes in integrating thermal signals, as works in Arabidopsis and several other plant species have demonstrated that changes in transcript levels of FT ‐like genes always correlate with flowering phenotypes induced by high temperatures (Abelenda et al, 2023; del Olmo et al, 2019; Kumar and Wigge, 2010; Nakano et al, 2013; Noy‐Porat et al, 2013). These results highlight the importance of transcriptional regulation of FT ‐like genes in thermal‐controlled flowering.…”
Section: Organism Temperature Change Typical Accession Impact On Flow...mentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies reveal that the INO80 complex mediates the eviction of H2A.Z and consequently activates the expressions of thermo-responsive genes, thereby contributing thermal morphogenesis of Arabidopsis ( Xue et al, 2021 ). Heat stress regulates plant flowering time by altering the deposition of H2A.Z on FT gene, whereas this regulatory effect is specific in different plant species ( Del Olmo et al, 2019 ; Abelenda et al, 2023 ). In conclusion, current researches on functions of histone variants in plants response to stresses have been focused on the H2A variants, and further investigations are needed to reveal the functions of other histone variants.…”
Section: Biological Functions Of Histone Variants In Plantsmentioning
confidence: 99%